Single-Layered Paper-Based Microfluidic Devices Made by Paint-Spraying Technique with Great Barrier Resistance for Colorimetric Assays - Nie,Beixi (2021)
The single-layered paint-spraying paper based microfluidic devices (sp-μPADs) have been for the first time integrated with the colorimetric assay. The polymethyl methacrylate (PMMA) board was applied as the mask instead of the iron mask, reducing the power requirement of the cutting machine. The paint was sprayed into the paper, which blocked the pores of the paper and constructed the hydrophobic barrier on the paper. The paint barrier was highly resistant to the various kind of chemicals and the minimum channel dimensions was 1.4 mm. By using the PMMA masks with different designs, the sp-μPADs with different designs have been fabricated and successfully applied to the single analyte assay of iron or bovine serum albumin (BSA) and the simultaneous assay of copper and nickel. Moreover, the feasibility of the multiplexed assay of eight analytes was also demonstrated. The analytical performances indicated that the fabricated sp-μPADs offered a promising platform in the colorimetric assays of either single or multiple analytes.